An annotated catalogue of Aloe and Aloiampelos (Asphodelaceae subfam. Alooideae) naturalised and escaped in continental Portugal - Smith, Gideon F.; Figueiredo, Estrela; Verloove, Filip; Klopper, Ronell R.; Silva, Vasco (Phytotaxa, 2023)
Three species of Aloe, namely A. arborescens, A. maculata, and A. vera, have been formally recorded as naturalised in the region covered by the Flora iberica project, which includes the Iberian Peninsula [Portugal and Spain] and the Balearic islands [an archipelago of islands and islets off the east coast of Spain, in the western Mediterranean Sea]. All three species occur in both Portugal and Spain. At least one further aloe, A. ×nobilis, is here formally recorded as naturalised in Portugal. We provide an updated, annotated catalogue of the alooids naturalised or escaped in Portugal, the southwestern-most country included in the Flora iberica project. Apart from these four naturalised taxa in Aloe, Aloiampelos ciliaris var. ciliaris, is also recorded as having escaped from cultivation.